Biting Divagations – Self-discoveries in Ian McEwan’s Black Dogs - Chalupský, Petr (American & British Studies Annual, 2010)
This article aims to explore the position of Ian McEwan’s novel Black Dogs (1992) within the corpus of his work. It attempts to show how this small in scale yet complex novel both follows and subverts the author’s characteristic themes and narrative strategies. It will also argue that, as the novel’s central concerns are the coming to terms with one’s past and the role of memory in this process, it in many respects anticipates McEwan’s most acclaimed work so far, Atonement (2001). Written soon after the fall of the Berlin Wall, Black Dogs ranks among his most politically engaged novels. Therefore, a special focus will be put on the author’s treatment of the theme of the often ambivalent relationship between private responsibility and public involvement that he touched upon in The Child in Time (1987) and later returned to in Amsterdam (1998).